1989
DOI: 10.1002/j.1460-2075.1989.tb08341.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the saccharide-binding site of concanavalin A.

Abstract: A complex of concanavalin A with methyl alpha‐D‐mannopyranoside has been crystallized in space group P212121 with a = 123.9 A, b = 129.1 A and c = 67.5 A. X‐ray diffraction intensities to 2.9 A resolution have been collected on a Xentronics/Nicolet area detector. The structure has been solved by molecular replacement where the starting model was based on refined coordinates of an I222 crystal of saccharide‐free concanavalin A. The structure of the saccharide complex was refined by restrained least‐squares meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(200 citation statements)
references
References 25 publications
10
189
0
1
Order By: Relevance
“…Substitution of N156 with A or Mutation of AD120I 121 to VA Prevents Binding to a Mannose Column Structural analysis by high resolution x-ray crystallography of legume lectins co-crystallized with their appropriate ligands has shown that the two conserved residues corresponding to D121 and N156 in ERGIC-53 (see Figure 1) interact via hydrogen bonds with the calcium ion and the monosaccharide (Derewenda et al, 1989;Bourne et al, 1990;Shaanan et al, 1991). The role of the conserved asparagine in carbohydrate binding was previously tested by its substitution with aspartate in the bean lectin Phaseolus vulgaris leucoagglutinin (PHA-L), and in pea lectin.…”
Section: Ergic-53 Mutants Containing An N-terminalmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of N156 with A or Mutation of AD120I 121 to VA Prevents Binding to a Mannose Column Structural analysis by high resolution x-ray crystallography of legume lectins co-crystallized with their appropriate ligands has shown that the two conserved residues corresponding to D121 and N156 in ERGIC-53 (see Figure 1) interact via hydrogen bonds with the calcium ion and the monosaccharide (Derewenda et al, 1989;Bourne et al, 1990;Shaanan et al, 1991). The role of the conserved asparagine in carbohydrate binding was previously tested by its substitution with aspartate in the bean lectin Phaseolus vulgaris leucoagglutinin (PHA-L), and in pea lectin.…”
Section: Ergic-53 Mutants Containing An N-terminalmentioning
confidence: 99%
“…Figure 6 shows that in the absence of divalent cations ERGIC-53 myc/6xHis failed to bind to the mannose column, while in the (Sharon and Lis, 1990;Sharon, 1993 (Derewenda et al, 1989;Bourne et al, 1990;Sharon and Lis, 1990;Shaanan et al, 1991). In the case of concanvalin A, removal of the cations by EDTA widens the binding site (Reeke et al, 1978), an effect that explains the loss of ligand binding in the absence of cations (Kalb and Levitzki, 1968).…”
Section: Elution Of Ergic-53 Is Selective For D-mannosementioning
confidence: 99%
“…These conditions are as previously described (Derewenda et al, 1989). These crystallization conditions are as identical as possible to those for the saccharide-free (I222) crystals.…”
Section: Crystallandation Data Collection and Processingmentioning
confidence: 99%
“…The model for the tetramer from Derewenda et al (1989), PDB coordinate file 4CNA, was treated as a molecular-replacement solution for the present study. The starting R factor was 45%.…”
Section: Model Refinementmentioning
confidence: 99%
See 1 more Smart Citation